2020
DOI: 10.3390/pathogens9050344
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Porcine Circovirus 3 Strains Circulating in Sardinian Pigs and Wild Boars

Abstract: Porcine circovirus 3 (PCV3) is a recently discovered member of the Circoviridae family. So far, its presence has been reported in North America, Asia, South America, and Europe. In this study, blood and tissue samples from 189 Sardinian suids (34 domestic pigs, 115 feral free ranging pigs, and 39 wild boars) were used to genetically characterize the PCV3 strains from Sardinia. PCV3 infection in the animals was confirmed by real time PCR. The detection rate in the three groups analyzed was l7.64% in domestic pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
3
18
1
Order By: Relevance
“…The presence of PRRSV or M. hyopneumoniae genome was subsequently screened using commercial real-time PCR kits, LSI VetMAX™ PRRSV EU/NA and VetMAX™-Plus qPCR Master Mix (both Thermo Fisher Scientific), respectively. The presence of PCV2 was instead evaluated by qualitative real-time PCR, as we previously described [44], using forward primer 5 -TGGCCCGCAGTATTCTGATT-3 and reverse primer 5 -CAGCTGGGACAGCAGTTGAG-3 [45]. Samples with Ct values less than 40 were considered positive [44].…”
Section: Dna/rna Extraction and Detection Of Pcv2 Prrsv Mycoplasma Hyopneumoniae Genomementioning
confidence: 99%
“…The presence of PRRSV or M. hyopneumoniae genome was subsequently screened using commercial real-time PCR kits, LSI VetMAX™ PRRSV EU/NA and VetMAX™-Plus qPCR Master Mix (both Thermo Fisher Scientific), respectively. The presence of PCV2 was instead evaluated by qualitative real-time PCR, as we previously described [44], using forward primer 5 -TGGCCCGCAGTATTCTGATT-3 and reverse primer 5 -CAGCTGGGACAGCAGTTGAG-3 [45]. Samples with Ct values less than 40 were considered positive [44].…”
Section: Dna/rna Extraction and Detection Of Pcv2 Prrsv Mycoplasma Hyopneumoniae Genomementioning
confidence: 99%
“…It is worth noting that the co-infections of PCV3 with PCV2 and/or PPV were common in both domestic and wild boars [70]. Dei et al evaluated blood and tissue samples from 189 Sardinian suids (34 domestic pigs, 115 feral free-ranging pigs, and 39 wild boars) and found that the infection rates of PCV3 in the three groups were 17.64%, 77.39%, and 61.54%, respectively [70]. Moreover, whether co-infection is related to more severe clinical symptoms needs to be further clarified.…”
Section: Co-infectionmentioning
confidence: 99%
“…Complete genome sequence of PCV3 isolate WB‐33 was compared with 83 complete genome sequences of PCV3 obtained from pigs and wild boars retrieved from GenBank (Figure 3c). PCV3 phylogenetic analysis showed that the PCV3 isolate WB‐33 is closely related to PCV3 genomes recovered from wild boars in Brazil (Varela et al., 2020), Italy (Dei Giudici et al., 2020) and Spain (Klaumann et al., 2019) and sequences recovered from domestic pigs in China, Denmark, Germany and Italy.…”
Section: Resultsmentioning
confidence: 98%